TINJAUAN SOSIO YURIDIS PERKELAHIAN ANTAR PEMUDA DI KELURAHAN BOMBONAWULU KECAMATAN GU KABUPATEN BUTON TENGAH - La Ode Bunga Ali; Hardi Done; Siti Afifa Hatma (Fakultas Hukum Universitas Dayanu Ikhsanuddin, 2023)
This study aims to determine the factors of the occurrence of fights between youths in Gu District, Bombonawulu Village and the efforts of the police to prevent fights between youths. This research was conducted in Buton Tengah District, Gu District with the research location in Bombonawuu Village. Data collection techniques through direct interviews with related parties from the results found the fact that the factors for the occurrence of fights between youths were education, family environment, age factor, revenge factor, liquor, lack of self-development forum in adolescents. Adapting police efforts and understanding to thr community about preventive efforts, taking prevention by actively engaging with the community and taking action against perpetrators of fights.